2018
DOI: 10.1017/jfm.2018.786
|View full text |Cite
|
Sign up to set email alerts
|

Boundary streaming by internal waves

Abstract: Damped internal wave beams in stratified fluids have long been known to generate strong mean flows through a mechanism analogous to acoustic streaming. While the role of viscous boundary layers in acoustic streaming has thoroughly been addressed, it remains largely unexplored in the case of internal waves. Here we compute the mean flow generated close to an undulating wall that emits internal waves in a viscous, linearly stratified twodimensional Boussinesq fluid. Using a quasi-linear approach, we demonstrate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…We speculate that there exists a continuous transition from our streaming mechanism at lateral (vertical) walls to the streaming mechanism over a flat bottom, recently investigated by Renaud & Venaille (2018). The viscous boundary layer description by Kistovich & Chashechkin (1995b,a) for supercritical internal waves reflecting at inclined boundaries may be a good starting point to extend the lateral-wall streaming analysis to oblique wave beam reflections at inclined boundaries.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…We speculate that there exists a continuous transition from our streaming mechanism at lateral (vertical) walls to the streaming mechanism over a flat bottom, recently investigated by Renaud & Venaille (2018). The viscous boundary layer description by Kistovich & Chashechkin (1995b,a) for supercritical internal waves reflecting at inclined boundaries may be a good starting point to extend the lateral-wall streaming analysis to oblique wave beam reflections at inclined boundaries.…”
Section: Discussionmentioning
confidence: 70%
“…Strong mean flow generation is known to occur due to horizontal cross-beam variation (Bordes et al 2012;Kataoka & Akylas 2015;Semin et al 2016;Beckebanze et al 2018b), with important modifications by planetary rotation (Grisouard & Bühler 2012;Fan et al 2018), and upon reflection where incident and reflected beams interact (Thorpe 1997;Grisouard et al 2013;Zhou & Diamessis 2015;Raja 2018). Renaud & Venaille (2018) recently also found strong mean flow generation in a flat bottom boundary layer.…”
Section: Introductionmentioning
confidence: 81%
“…When the same vertical velocity is imposed on both sides of the boundary, corresponding to the oscillations of a rigid plate, the present analysis for n = 1 yields a boundary layer of the same order as the waves; the same conclusion has been reached by Hurley & Hood (2001) using a free-slip boundary condition. When a given vertical velocity profile is imposed on part of an otherwise fixed boundary, as for the wave generator in § 8.3, and the image of the profile through this boundary is added, the present analysis for n = 0 predicts that the boundary layer is negligible compared with the waves; for an undulating horizontal wall, the boundary layer has been found by Renaud & Venaille (2019) to be negligible compared with the waves when a free-slip boundary condition is used, and of the same order as them when a no-slip condition is used.…”
Section: 3mentioning
confidence: 78%
“…The particular case of a two-dimensional horizontal boundary has been considered by Hurley & Hood (2001) and Renaud & Venaille (2019). When the same vertical velocity is imposed on both sides of the boundary, corresponding to the oscillations of a rigid plate, the present analysis for yields a boundary layer of the same order as the waves; the same conclusion has been reached by Hurley & Hood (2001) using a free-slip boundary condition.…”
Section: Line Forcingmentioning
confidence: 99%
“…It has been also recently shown that viscous boundary layers can induce strong mean flow due to streaming (Horne et al. 2019; Renaud & Venaille 2019).…”
Section: Introductionmentioning
confidence: 99%